The structural relationship between achievement goal orientation and perceived performance among swimmers: a chain multiple mediation model - Zhu, Yuanjiao; Zhang, Weipeng; Liu, Hao; Song, Huitao (Frontiers in Psychology, 2025)
BackgroundAchievement goal orientation (AGO) has been identified as an important determinant of Perceived Performance (PP) in athletes. However, there is limited research analyzing this relationship through multiple mediation models.MethodsIn this study, data from 377 competitive swimmers (45.1% female, 54.9% male, aged 18–22 years old) from Tianjin and Beijing universities were collected through questionnaires, and structural equation modelling (SEM) was used to analyze the relationship between AGO, Sports Enthusiasm (SE), Sports Commitment (SC), and Grit and PP.ResultsAGO significantly elevated PP (β = 0.116, p ≤ 0.001), explaining 76.6% of the total effect of AGO on PP through the chain-mediated effects of SE (β = 0.472, p ≤ 0.001), SC (β = 0.448, p ≤ 0.001) and Grit (β = 0.165, p ≤ 0.001).ConclusionThe chain mediation model of this study suggests that AGO enhances swimmers ‘PP through SE, SC, and Grit, guiding coaches’ goal setting, swimmers ‘progress tracking, and psychologists’ reassessment strategies.